SWOT analysis of professional practices of Social Education in social services: possibilities and limits - Varela Crespo, Laura (Revista Complutense de Educación, 2021)
The article presents an analysis of educational practices of social educators in social services, focusing on the study of issues that are internal and external to the functioning of these services that facilitate or limit the possibilities of developing quality socio-educational action. The paper is based on qualitative research carried out with 14 social educators and 10 experts in the field of social services, carrying out -through an online questionnaire- a SWOT analysis to investigate the factors that influence the development of socio-educational actions aimed at training people in tasks that enable them to gain greater autonomy and expand their family and community support networks. The results show the presence of limitations to carry out Social Education in social services linked to the lack of investment in social policy, excessive bureaucratization and centralization of services, lack of coordination in work teams or to the absence of a socio-educational perspective in the actions carried out. Networking is perceived as the main opportunity for the improvement of socio-educational practices in social services, highlighting motivation and professional commitment as a strength. The conclusions point out that both the social educators and the group of experts agree on the need to strengthen the socio-educational networks in the territories in order to improve the functioning of social services and promote citizen initiative. Further reflection on professional practice is considered necessary, given that limitations do not only derive from external factors, but also from internal aspects of the profession (continuous training, establishment of common criteria for action, etc.).
Keywords: community education; social services; career development; intervention; SWOT analysis